Understanding antibiotic‐seeking behaviour: A qualitative case study of mothers of children aged 5 and under. (21st July 2022) - Bosley, Helen; Henshall, Catherine; Appleton, Jane V.; Jackson, Debra
Abstract: Background: Antibiotics savelives and have been effectively and reliably used for decades to treat infections and improve health outcomes. This trust in antibiotics has contributed to over prescribing and the emergence of antimicrobial resistance. Significant amounts of antibiotics are still widely prescribed and taken, especially in young children. However, there is a paucity of existing literature relating to how mothers, who are the main carers of young children, may be influenced by their trust in antibiotics. Aims: To explore what factors influence mothers' decisions to seek antibiotics for their young children. Design: Qualitative case study using postcode boundaries. Methods: Thematic analysis of qualitative data from mothers of children under 5, recruited via community playgroups within the case. Data were collected between October 2018 and May 2019, from six focus groups ( n  = 19) and one‐to‐one interviews ( n  = 14). Thematic analysis of the data consisted of six phases: data familiarization; generating initial codes; searching for themes; reviewing themes; defining and naming themes; and producing the report. Results: Mothers were influenced by their belief and trust in antibiotics. Antibiotics were identified as symbolic of recovery, healing and of providing protection and safety. Conclusion: By understanding the symbolic power of antibiotics on maternal decision making, all antibiotic prescribers may be able to offer and provide reassuring alternative and acceptable treatment options to mothers, rather than using antibiotics. Impact: This paper introduces the concept of antibiotics as powerful symbols which influence antibiotic seeking behaviour. This in turn may result in inappropriate use of antibiotics which contributes to the risk of antimicrobial resistance developing. Although the majority of antibiotics are still prescribed by doctors, the number of nurse prescribers has been increasing. Therefore, an increased awareness of antibiotic symbolism, in all prescribing clinicians, is important to enable future local and national strategies to be developed, to support maternal decision making and reduce antibiotic seeking behaviour.